The occurrence of autoantibodies in patients with chronic HCV infection, including patients dialyzed and after kidney transplantation - Łapiński, Tadeusz W.; Rogalska-Płońska, Magdalena; Parfieniuk-Kowerda, Anna; Świderska, Magdalena; Flisiak, Robert (Clinical and Experimental Hepatology, 2016)
Introduction: There are reports suggesting that hepatitis C virus (HCV) may stimulate the autoimmune process. Studies have been undertaken to evaluate the occurrence and type of autoantibodies in HCV-infected patients with and without immunosuppression. Results were analyzed according to HCV genotype, intensity of inflammation and liver fibrosis stage. Material and methods: The study included 105 patients chronically infected with HCV, including 25 with immunological suppression administered for kidney disease or kidney transplantation. Blood samples were tested by immunoblotting for the presence of AMA-M2, SLA/LP, LKM-1, LC1, anti-F-actin, anti-desmin, anti-myosin, anti-gp210 and anti-sp100 autoantibodies, and ANA. All the patients were scored for autoimmune hepatitis. Results : Autoantibodies were detected in 32.5% of patients without immunosuppression and in 16% with immunosuppression. Single types of autoantibodies were identified in 26% of patients. The most frequent ones were ANA (19%) and AMA-M2 (5.7%). The presence of antibodies in patients with genotype 1 was significantly higher in comparison to their occurrence in genotype 3. Autoimmune hepatitis was not diagnosed in any of the patients. Immunoglobulin G level was significantly higher in patients with detectable autoantibodies, compared to patients without antibodies (1.89 vs. 1.28 g/dl, p < 0.001). No correlation between fibrosis stage or intensity of inflammatory state and the frequency of antibodies was found. Conclusions : The antibodies are significantly more frequent in patients without immunosuppression and in patients infected with genotype 1 than genotype 3. The presence of these autoantibodies is not associated with the development of autoimmune hepatitis. Higher level of immunoglobulin G in the serum correlates with the presence of autoantibodies.